Advocacy Coalition in The Arrangement of The Coastal Slum Area of Untia in Makassar - Rusnaedy, Zaldi; Haris, Almuhajir (Universitas Muhammadiyah Yogyakarta, 2021)
The arrangement of the slum settlement area is still a problem faced by the Makassar City Government. There are 740.10 hectares of slum areas in Makassar City, one of which is the Untia coast. This study aimed to analyze the advocacy coalition in slum area management. The research method used was a qualitative method. The results showed that at the beginning of 2019, Untia had become a light slum area from the previous heavy slum. This happened because Untia received many programs from the government for a relatively long time. This activity was a collaborative activity of several government institutions and Kotaku government agencies that are members of the Working Group (Pokja). Therefore, Untia is still in the category of a slum area, not because of a lack of assistance from the government, but rather because the programs implemented are not integrated. So, the result was that the settlements that receive the program only come out of the slum indicator partially. In addition, the institutions involved in the Working Group (Pokja) often overlap programs due to a lack of face-to-face communications.